TTY2: A Multicopy Y-Linked Gene Family - Makrinou, Eleni; Fox, Margaret; Lovett, Michael; Haworth, Kim; Cameron, Jessie M.; Taylor, Kay; Edwards, Yvonne H.

(untitled) (Genome Research, 2001)
Genes involved in human male sex determination and spermatogenesis are likely to be located on the Y chromosome. In an effort to identify Y-linked, testis-expressed genes, a cDNA selection library was generated by selecting testis cDNA with Y-cosmid clones. Resultant clones containing repetitive or vector material were eliminated, and 79 of the remaining clones were sequenced. Nineteen cDNAs showed homology with the TTY2 gene, and indicated that TTY2 is part of a large gene family. Screening of a panel of Y-linked cosmids revealed that the TTY2 gene family includes at least 26 members organized in 14 subfamilies. Further investigation revealed that TTY2 genes are arranged in tandemly arrayed clusters on both arms of the Y chromosome, and each gene comprises a series of tandemly arranged repeats. RT-PCR studies for two of these genes revealed that they are expressed in adult and fetal testis, as well as in the adult kidney. None of the genes investigated in detail contain an open reading frame. We conclude that the TTY2 gene family is composed of multiple copies, some of which may function as noncoding RNA transcripts and some may be pseudogenes.[The sequence data described in this paper for TTY2L12A and TTY2L2A have been submitted to the EMBL data library, under accession nos.AJ297963 and AJ297964.]